PENDAMPINGAN PENERAPAN TEKNOLOGI SMART FISH FARM BUDIDAYA IKAN KOI PADA DINATA KOI FARM BADUNG: ASSISTANCE IN THE IMPLEMENTATION OF SMART FISH FARM TECHNOLOGY CULTIVATING KOI FISH AT DINATA KOI FARM BADUNG - I Wayan Widi Karsana; Putu Andhika Kurniawijaya (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Dinata Koi Farm is a Koi fish cultivation business that has been started since 2018. The Koi fish cultivation business is carried out starting from breeding, sorting, growing and marketing Koi fish. The demand for Koi fish orders by customers is not proportional to the amount of production produced. The problem is that many fish die due to poor water quality, thereby reducing the number of Koi fish produced for market. Koi fish are very sensitive to increases in temperature and pH levels of pond water. Dinata Koi Farm has a problem, namely that it cannot continuously monitor the temperature and pH levels of the water, so sometimes handling the pond water quality becomes slow and the Koi fish die. Based on the problems faced by partners, the service team helped develop smart fish farming technology that can monitor Koi pond water quality in real time and automatically handle it if there is an increase in the temperature and pH levels of the pond water. . The approach methods that will be used in this activity include individual approaches and training. The components evaluated in this activity are the application of smart fish farm technology and increasing partners' knowledge in the use of information technology, especially smart fish farms.